0
$\begingroup$

An exercise says : Use algebraic manipulation to find the mimimum SOP expression for the function $$f = x_1x_3 + x_1x_2' + x_1'x_2x_3 + x_1'x_2'x_3'$$

The given solution says:

$f = x_1x_3 + x_1x_2' + x_1'x_2x_3 + x_1'x_2'x_3'\\ = x_1(x_2' + x_2)x_3 + x_1x_2'(x_3' + x_3) + x_1'x_2x_3 + x_1'x_2'x_3'\\ = x_1x_2'x_3 + x_1x_2x_3 + x_1x_2'x_3' + x_1'x_2x_3 + x_1'x_2'x_3'\\ = x_1x_3 + (x_1 + x_1')x_2x_3 + (x_1 + x_1')x_2'x_3'\\ = x_1x_3 + x_2x_3 + x_2'x_3'$

In the last two equalities, how $x_1x_3$ showed up?

$\endgroup$
1
$\begingroup$

$\color{red}{x_1x_2'x_3+x_1x_2x_3}+\color{blue}{x_1x_2'x_3'}+\color{green}{x_1'x_2x_3}+\color{blue}{x_1'x_2'x_3'}\\=\color{red}{x_1x_2'x_3+x_1x_2x_3}+\color{green}{x_1x_2x_3}(*)+\color{blue}{x_1x_2'x_3'}+\color{green}{x_1'x_2x_3}+\color{blue}{x_1'x_2'x_3'}\\=\color{red}{x_1(x_2+x_2')x_3}+\color{blue}{(x_1+x_1')x_2'x_3'}+\color{green}{(x_1+x_1')x_2x_3}\\=x_1x_3+x_2'x_3'+x_2x_3$

$(*)$ due to the Idempotent Law, $A=A+A\implies x_1x_2x_3=x_1x_2x_3+x_1x_2x_3$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.